The Quebec emergency department guide: A cross-sectional study to evaluate its use, perceived usefulness, and implementation in rural emergency departments. Issue 1 (7th December 2017) - Fleet, Richard; Hegg-Deloye, Sandrine; Maltais-Giguère, Julie; Légaré, France; Ouimet, Mathieu; Poitras, Julien; Tanguay, Alain; Archambault, Patrick; Levesque, Jean-Frédéric; Simard–Racine, Geneviève; Dupuis, Gilles
Abstract: Objectives: The Quebec Emergency Department Management Guide (QEDMG) is a unique document with 78 recommendations designed to improve the organization of emergency departments (EDs) in the province of Quebec. However, no study has examined how this guide is perceived or used by rural health care management. Methods: We invited all directors of professional services (DPS), directors of nursing services (DNS), head nurses (HN), and emergency department directors (EDD) working in Quebec's rural hospitals to complete an online survey (144 questions). Simple frequency analyses (percentage [%] and 95% confidence interval) were conducted to establish general familiarity and use of the QEDMG, as well as perceived usefulness and implementation of its recommendations. Results: Seventy-three percent (19/26) of Quebec's rural EDs participated in the study. A total of 82% (62/76) of the targeted stakeholders participated. Sixty-one percent of respondents reported being "moderately or a lot" familiar with the QEDMG, whereas 77% reported "almost never or sometimes" refer to this guide. Physician management (DPS, EDD) were more likely than nursing management (DNS and especially HN) to report "not at all" or "little" familiarity on use of the guide. Finally, 98% of the QEDMG recommendations were considered useful. Conclusions: Although the QEDMG is considered a useful guide for rural EDs, it is not optimally known or used in rural EDs, especially by physician management. Stakeholders should consider these findings before implementing the revised versions of the QEDMG. RÉSUMÉ: Objectif: Le Guide de gestion de l'urgence au Québec est un document unique en son genre, qui contient 78 recommandations visant à améliorer l'organisation des services d'urgence (SU) dans la province de Québec. Toutefois, aucune étude n'a porté sur la manière dont le Guide est perçu ou appliqué par les gestionnaires des soins de santé en région. Méthode: Tous les directeurs des services professionnels (DSP), directeurs des soins infirmiers (DSI), infirmières-chefs (IC) et directeurs des services d'urgence (DSU) travaillant dans des hôpitaux situés en région, au Québec, ont été invités à répondre à une enquête en ligne (144 questions). Nous nous sommes appuyés sur de simples analyses de la fréquence (pourcentage [%] et intervalles de confiance à 95 %) pour établir le degré général de connaissance du Guide et de son application ainsi que pour déterminer le degré de perception de son utilité et l'état de la mise en œuvre des recommandations. Résultats: Dans l'ensemble, 73 % (19/26) des SU situés en région, au Québec, ont participé à l'étude, de même que 82 % (62/76) des parties ciblées. Soixante et un pour cent des répondants ont indiqué « bien connaître » ou « connaître assez bien » le Guide, tandis que 77 % ont indiqué se reporter « parfois » ou « presque jamais » au Guide. Les gestionnaires des soins médicaux (DSP, DSU) étaient plus nombreux que les responsables des soins infirmiers (DSI et surtout les IC) à indiquer qu'ils utilisaient ou connaissaient « peu » ou « pas du tout » le Guide. Enfin, 98 % des recommandations contenues dans le Guide étaient considérées comme utiles. Conclusions: Tandis que le Guide est considéré comme utile dans les SU situés en région, il n'est pas appliqué de la meilleure façon qui soit par les intervenants ou il est mal connu de ceux-ci, en particulier des gestionnaires des soins médicaux. Les différentes parties devraient donc tenir compte des résultats de l'étude avant la mise en œuvre des versions révisées du Guide.